CHARACTERIZATION OF THE TREE COMPONENT IN A SEMIDECIDUOUS FOREST IN THE ESPINHAÇO RANGE: A SUBSIDY TO CONSERVATION - Versieux, Leonardo de Melo (2011)
This study was conducted in the Private Reserve Mata do Jambreiro (912 ha), localized in the Iron Quadrangle, Minas Gerais, southeastern portion of the Espinhaço Range, which is predominantly covered by semideciduous seasonal montane forest. Three topographically and physiognomic similar areas located within a continuum forest fragment, distant by 1.3 to 1.5 km were sampled by the point-quadrat method. In each area, 30 points were marked. Individuals with a minimum perimeter at the breast height (PBH) of 15 cm were sampled, totaling 111 species belonging to 40 families. The most representative family was Fabaceae, with 14.29% of the total number of species. Low floristic similarity (5.3% to 34.4%) was observed between the areas, pointing out the importance of distribution of sample units in continuous fragments. Shannon diversity index (H') found was 4.22 and Pielou equability (J) 0.894. Soil analysis showed some differences in chemical composition between the three studied areas and was an important component for the interpretation of the floristic variation found. The low floristic similarity observed here for close areas justify the requirement of more detailed inventories by Brazilian Environmental Agencies for the legal authorization procedures prior to the establishment of new enterprising projects. Also, the professionals that conduct rapid inventories, mainly the Environmental Consultants, should give more attention to this kind of floristic variation and to the methods used to inventory complex forests.